Spanish comics historical and cultural perspectives - Magnussen, Anne 1964- (Berghahn, 2021)
"Spanish comics represent an exciting and diverse field, yet one that is often overlooked by scholars outside of Spain. Spanish Comics offers an overview on contemporary scholarship on Spanish comics, focusing on a wide range of comics dating from early comics history in 1875-1939; the Francoist dictatorship, 1939-1975; the Political Transition, 1970-1985; and Democratic Spain from the early 1980s. Touching on themes of memory, gender, regional identities, and history, the chapters in this collection demonstrate the historical and cultural significance of Spanish comics, particularly as it relates to transnational and memory studies"--
Keywords: Geschichte 1875-1990; Comic; Spanisch; Comic books, strips, etc / Spain / History and criticism; Comic books, strips, etc; Spain; Criticism, interpretation, etc; Aufsatzsammlung